Visual deficits in anisometropia - Levi, Dennis M. (2010)
Amblyopia is usually associated with the presence of anisometropia, strabismus or both early in life. We set out to explore quantitative relationships between the degree of anisometropia and the loss of visual function, and to examine how the presence of strabismus affects visual function in observers with anisometropia. We measured optotype acuity, Pelli-Robson contrast sensitivity and stereoacuity in 84 persons with anisometropia and compared their results with those of 27 persons with high bilateral refractive error (isoametropia) and 101 persons with both strabismus and anisometropia. All subjects participated in a large scale study of amblyopia (McKee, Levi & Movshon, 2003). We found no consistent visual abnormalities in the strong eye, and therefore report only on vision in the weaker, defined as the eye with lower acuity. LogMAR acuity falls off markedly with increasing anisometropia in non-strabismic anisometropes, while contrast sensitivity is much less affected. Acuity degrades rapidly with increases in both hyperopic and myopic anisometropia, but the risk of amblyopia is about twice as great in hyperopic than myopic anisometropes of comparable refractive imbalance. For a given degree of refractive imbalance, strabismic anisometropes perform considerably worse than anisometropes without strabismus – visual acuity for strabismics was on average 2.5 times worse than for non-strabismics with similar anisometropia. For observers with equal refractive error in the two eyes there is very little change in acuity or sensitivity with increasing (bilateral) refractive error except for one extreme individual (bilaterally refractive error of -15 D). Most pure anisometropes with interocular differences less than 4 D retain some stereopsis, and the degree is correlated with the acuity of the weak eye. We conclude that even modest interocular differences in refractive error can influence visual function.